1999
DOI: 10.1152/ajpheart.1999.276.6.h1861
|View full text |Cite
|
Sign up to set email alerts
|

Peroxynitrite contributes to spontaneous loss of cardiac efficiency in isolated working rat hearts

Abstract: We examined the mechanism of the time- and protein synthesis-dependent decline in cardiac mechanical function in isolated working rat hearts. Hearts were perfused with Krebs-Henseleit buffer for 120 min in the presence or absence of the protein synthesis inhibitor cycloheximide (CX; 10 μM). Cardiac work remained stable for 60 min and then spontaneously decreased during 60–120 min of perfusion. This was accompanied by an increase in myocardial inducible nitric oxide synthase (iNOS) and xanthine oxidase (XO) act… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
39
0

Year Published

2000
2000
2018
2018

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 52 publications
(41 citation statements)
references
References 30 publications
2
39
0
Order By: Relevance
“…Formation of dityrosine has been attributed mainly to the activation of the myeloperoxidase/H 2 O 2 system of neutrophils and macrophages (46), but other peroxidases (47) and peroxynitrite (36, 48) have been recognized as additional sources of dityrosine. The present results agree with previous studies suggesting that dityrosine formation together with increased NO synthase expression may be a useful marker for peroxynitrite formation in tissues (49,50).…”
Section: Peroxynitrite-mediated Tyrosine Modificationsupporting
confidence: 93%
“…Formation of dityrosine has been attributed mainly to the activation of the myeloperoxidase/H 2 O 2 system of neutrophils and macrophages (46), but other peroxidases (47) and peroxynitrite (36, 48) have been recognized as additional sources of dityrosine. The present results agree with previous studies suggesting that dityrosine formation together with increased NO synthase expression may be a useful marker for peroxynitrite formation in tissues (49,50).…”
Section: Peroxynitrite-mediated Tyrosine Modificationsupporting
confidence: 93%
“…Activity of xanthine oxidase and xanthine dehydrogenase is increased by nitrite during ischemic conditions, where oxygen and pH are reduced, but not during aerobic conditions. Increased xanthine oxidoreductase activity as a consequence of ischemia has been reported previously [33][34][35][36]. Alternately, ischemia may repair the inactive desulfo form of the enzyme to the fully active form as previously suggested [25].…”
Section: Discussionmentioning
confidence: 55%
“…There are many studies which demonstrate a concentration-dependent biphasic effect of peroxynitrite on basal myocardial contractility, but the majority of these studies did not address these effects on β-adrenergic responsiveness [10][11][12][13][14][15][16][17][18]26,28]. In our study, SIN-1 (source of peroxynitrite) had a biphasic effect on murine cardiomyocyte contractility that was not only dependent on concentration, but also on the contractile state of the cardiomyocyte.…”
Section: Discussionmentioning
confidence: 60%
“…For instance, numerous studies have shown high concentrations of peroxynitrite to be detrimental to myocardial contractility [10][11][12][13][14][15], while at low concentrations peroxynitrite appears to act as a positive inotropic agent [16][17][18]. However, the majority of these studies examined effects on basal contractility and did not address the effects of peroxynitrite as they relate to β-adrenergic responsiveness.…”
Section: Introductionmentioning
confidence: 99%